Intramolecular pyridine-based frustrated Lewis-pairs. Issue 21 (8th May 2015) - Körte, Leif A.; Warner, Robin; Vishnevskiy, Yury V.; Neumann, Beate; Stammler, Hans-Georg; Mitzel, Norbert W.
Abstract : Besides a series of pyridine-based Lewis pairs with B(C6 F5 )2 groups with varying electronic and steric situations and strong intramolecular B–N bonds, 2-[(CH2 )4 B(C6 F5 )2 ]-6- t Bu-pyridine was found to behave as a frustrated Lewis pair. Abstract : Deprotonation of the methylpyridines 2, 6-lutidine, 2-picoline, 4-dimethylamino-2, 6-dimethylpyridine as well as 2, 6-dimethyl-4-(piperidine-1-yl)pyridine with n -butyllithium or n -butyllithium/KO- t -Bu at the methyl positions led to the corresponding organolithium or -potassium compounds. Treatment with ClB(C6 F5 )2 resulted in formation of the 2-borylmethylpyridines py-CH2 -B(C6 F5 )2 . They are monomeric and form intramolecular B–N bonds and four-membered rings. A short intramolecular B–N distance was observed in the crystal structure of the dimethylamino-functionalized derivative and proposed to be responsible for the low reactivity of the products towards hydrogen, thf, acetonitrile and CO2 . Hydroboration of 6- tert -butyl-2-but-4′-enylpyridine with HB(C6 F5 )2 led to the corresponding hydroboration product t -Bu-py-(CH2 )4 -B(C6 F5 )2 which shows no intramolecular B–N bond formation due to steric crowding. H/D-scrambling experiments with a H2 /D2 mixture revealed its reactivity towards hydrogen.